The Role Of The Armenian Community In UAE-Armenia Relations - Menkechian, Chake (ՀՀ ԳԱԱ)
This paper explores the important role of the Armenian community residing in the United Arab Emirates (UAE) in strengthening bilateral relations between the UAE and Armenia. It highlights the contributions of the Armenian community in UAE to diplomatic relations and the promotion of Armenian culture in the region. The study also emphasizes the cultural programs organized by the embassies and the importance of fostering intellectual dialogue between Armenian and Emiratis. It discusses potential areas for collaboration in the diplomatic sphere between the Republic of Armenia (RA) and the UAE as well as the favourable business environment for UAE companies in Armenia.
Keywords: International relations